1999
DOI: 10.1088/0953-8984/12/1/306
|View full text |Cite
|
Sign up to set email alerts
|

Study of indium-defect interactions in diamond using two-dimensional conversion-electron emission channelling

Abstract: Channelling has, since its inception, proven to be a valuable tool in locating the geometric position of atoms in the crystal lattice. Allied with powerful theoretical models, it can yield detailed information on the positions that these impurities occupy. 111 In, a radioactive isotope with a conveniently short half-life, is an often-used probe of heavy-atom doping of materials. Previous work has centred on the lattice location of 111 In implanted in type IIa diamond. Theoretical calculations on this `pure' sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Unfortunately, fast decay of many isotopes often leaves no time for postimplantation annealing in ion channeling experiments. The method has been successfully applied to Li, B, P, Ge, As, In, Cd, and Hf (Doyle et al 2000) ions implanted into natural and HPHT diamonds. Amazingly, high substitutional fractions, namely 70, 55, 54, and 34%, were observed for large (relative to carbon) As, P, Ge, and In atoms, respectively (Ronning and Hofsass 1999, Braunstein and Kalish 1981, Gorbatkin et al 1991, Correia et al 1997, but only ∼12% of implanted boron was found in substitutional sites (Ittermann et al 1997).…”
Section: Ion Channellingmentioning
confidence: 99%
“…Unfortunately, fast decay of many isotopes often leaves no time for postimplantation annealing in ion channeling experiments. The method has been successfully applied to Li, B, P, Ge, As, In, Cd, and Hf (Doyle et al 2000) ions implanted into natural and HPHT diamonds. Amazingly, high substitutional fractions, namely 70, 55, 54, and 34%, were observed for large (relative to carbon) As, P, Ge, and In atoms, respectively (Ronning and Hofsass 1999, Braunstein and Kalish 1981, Gorbatkin et al 1991, Correia et al 1997, but only ∼12% of implanted boron was found in substitutional sites (Ittermann et al 1997).…”
Section: Ion Channellingmentioning
confidence: 99%